2008
DOI: 10.1586/14737175.8.12.1829
|View full text |Cite
|
Sign up to set email alerts
|

What’s in the pipeline for the treatment of Parkinson’s disease?

Abstract: Parkinson's disease (PD) is a common, debilitating neurodegenerative disorder that creates a significant burden for patients, family members and society at large. Major unmet needs include effective therapies that could favorably modify the underlying pathogenetic processes in PD, and better control of motor and nonmotor symptoms in advanced-stage disease. This review examines the current state of development of potential PD therapies, including dopaminergic therapies, modulators of adenosine and glutamate rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…Of note, based on the neuroregenerative and neuroprotective properties of FKBP inhibitors, phase II clinical trials were recently performed with NI-IL. Neither in a 6 month nor in a 2 year trial with GPI-1485, a nonimmunosuppressive analog of FK506, improvements were seen in motor symptoms or DA neurotransmitter levels of patients with mild to moderate PD (Poulter et al, 2004;Sommer and Stacy, 2008). Several explanations are possible.…”
Section: Discussionmentioning
confidence: 98%
“…Of note, based on the neuroregenerative and neuroprotective properties of FKBP inhibitors, phase II clinical trials were recently performed with NI-IL. Neither in a 6 month nor in a 2 year trial with GPI-1485, a nonimmunosuppressive analog of FK506, improvements were seen in motor symptoms or DA neurotransmitter levels of patients with mild to moderate PD (Poulter et al, 2004;Sommer and Stacy, 2008). Several explanations are possible.…”
Section: Discussionmentioning
confidence: 98%
“…As a disease that occurs later in the patients' lives, PD has a high incidence and produces great burden on patients, families and society [22,23]. Moreover, the mechanism underlying the cognitive impairment in PD remains poorly understood [6], but recently, a study indicated that miRNAs play a significant role in PD [24].…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that UCH-L1 possesses E4 ubiquitin ligase activity, which promotes polyubiquitination of α-synuclein to pathologically alter basal turnover ( 8 ). Furthermore, it has been proposed that this interaction is mediated specifically by farnesylated UCH-L1 M ( 9 ), and, on the basis of this finding, small molecule farnesyltransferase inhibitor drugs such as LNK-754 are currently in clinical trials to inhibit or reduce the levels of farnesylated UCH-L1 M ( 29 , 30 ). Although our study does not preclude potential roles for FTIs in treating neurodegeneration, our data strongly suggest that they do not act by decreasing the membrane association of UCH-L1 M .…”
Section: Discussionmentioning
confidence: 99%